The Importance Of Implementing Financial Reporting Based On Sak EMKM In Improving MSMES Performance - Wildaniyati, Arini; Rohman, Fatchur; Suharni, Siti (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
One way to measure micro-small-medium enterprises’ (MSMEs) performance is by analyzing how they manage their financial reporting, that comply with the accounting standard for micro, small, medium entity (MSMEs), i.e. the Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (SAK EMKM). The standard performance was published in january 1, 2018. MSMEs in Madiun city area are one of MSME’s should implement this SAK. This research attempts to find the relationship between MSEMs financial management based on SAK EMKM and MSEMs performance. This study based on observation, survey, interview, and questionnaire. The questionnaire were distributed of 100 MSMEs owners in the City of Madiun, East Java, Indonesia. The analysis method use descriptive analysis and simple linier regresion. The results show that MSMEs owners believe that adherence to SAK-EMKM is very important for their business conducts. The analysis also shows that there is a significant effect of reporting and performance.